Durability of airport concrete pavement improved by four novel coatings. Issue 5 (16th March 2018) - Zhang, Jun; Weng, Xingzhong; Jiang, Le; Yang, Bohan; Liu, Junzhong; Qu, Bo
Abstract : In order to repair surface damage to airport pavements quickly and efficiently, surface-strengthening materials are applied to the surface of the concrete to improve its durability. In the current study, several materials, namely concrete protectant, polyurea, epoxy resin and silane, were applied to concrete samples in various amounts. One-sided freeze–thaw cycle experiments, wear tests and flame ablation tests, along with scanning electron microscopy to observe morphologies, were carried out on these four coatings and the uncoated samples to determine the best material for strengthening runway concrete. Results showed that polyurea had excellent wear resistance and poor flame ablation resistance. The epoxy resin had good resistance to freeze–thaw cycles and flame ablation, but had poor wear resistance. The protective layer of silane reduced the loss by freeze–thaw by 66% compared with non-coated samples, the relative dynamic elastic modulus increased by 64·8% and the unit area wear quality decreased by 41%, and there was no obvious damage to the samples after flame ablation. Silane is the most suitable material for surface improvement of the airport concrete pavement, with an optimum dosage of 4 m 2 /kg.